Pendidikan Afektif Dan Penerapannya Dalam Pembelajaran Di Sekolah - Tatik Safiqo (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2020)
The failure of religious education is because the practice of education only pays attention to the cognitive aspects of the growth of values ​​(religion), and ignores the development of affective and conative-volutive aspects, namely the ability and determination to practice the values ​​of religious teachings. As a result, there is a gap between knowledge and practice in religious teaching, so that they are unable to form an Islamic personality. The success of education, so far, is only measured from the superiority of the cognitive domain and barely measures the affective and psychomotor domains, so that character building and character are neglected. In order to anticipate these various problems, religious education learning in schools must show its contribution. One of them is improving. As for every material taught to students contains values ​​related to the behavior of everyday life, such as moral material, and for this moral aspect, in addition to studying the problems related to the knowledge aspect, the functional aspect is prioritized on the attitude aspect, so that later students behave as a Muslim who has a noble character. Then these affective values ​​are in the material of morals and must be embedded in students in Religious Education.